Assessing the potential for rainwater harvesting use in a concentrated animal feeding operation region in the south of Brazil - Hoss, C. (2022)
Sustainability in intensive animal production is directly linked to water management. The increasing pressure on water resources and the occurrence of increasingly frequent and severe droughts makes it harder to meet the demand for animal husbandry in rural properties and highlights the importance of rational water use and the search for alternative sources of water supply. In the midwest region of Santa Catarina state, south of Brazil, the use of cisterns to store rainwater collected from the roofs of houses that confine animals is an alternative already widely used and encouraged to minimize water scarcity. Studies that deal with the potential for rainwater use in livestock production are still scarce; however, available information provides a concrete basis for further technical and economic feasibility studies. The present study aimed to evaluate, based on local precipitation and available harvesting areas, the potential of the use of rainwater to supply the water demand (r, %) and the water-saving potential (R, m3/year) in swine and poultry Concentrated Animal Feeding Operations (CAFOs) in Jacutinga river basin and contiguous sub-basin municipalities, a region with great national importance in this activity. As a result, potential r values of 100% to supply water demand in the poultry sector and between 32.7% and 68.3% in the different production stages of the swine sector were obtained. The potential R value in the study area represented 5.2 million m3 per year. Such results reveal the high potential of rainwater harvesting systems not only for minimizing impacts of drought periods but also as an abundant source of water for supplying the husbandry water demand of rural farms, ensuring water security, and serving as a tool for managing local water resources.